PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP MINAT BELI SMARTPHONE XIAOMI - Julia Retnowulan (Cakrawala - Jurnal Humaniora, 2017)
The use of smartphones increasingly increasing in line with the increasing infrastructure of internet access to the entire territory of Indonesia. In addition, the price of smartphones are increasingly affordable and become a trend makes the use of smartphones reaching the corners of the archipelago. Indonesia as a country with the fourth largest population in the world, became a potential smartphone market share for smartphone manufacturers, all world-renowned brands compete fiercely seize the big smartphone market in Indonesia. This study aims to examine the factors that affect the buying interest of Xiaomi smartphones, namely product quality and price perception. The sample in this study consists of 94 students in ASM BSI Jakarta who have been using Xiaomi smartphone. Research data using primary data of questionnaire distributed result. The results showed that product quality significantly influence buying interest, price perception have significant effect to buying interest, product quality and price perception simultaneously have significant effect to buying interest.